The making of storage application for electronic official document based on microsoft access at document unit pt kai (persero) daop 2 bandung - Rena Puspitasari; Mohammad Rizal Gaffar (Ebiz Prima Nusa, 2024)
The document unit of PT KAI (Persero) Daop 2 Bandung has tasks and functions in managing company documents. One of the document management activities is storage. The file storage is inefficient because it is not stored centrally, and searching in the file explorer can only be done based on the document file name, resulting in a lengthy search process. To help overcome this issue, a Microsoft Access-based official document storage application has been developed. In addition to serving as a centralized storage location, this application also facilitates quick searches, generates reports based on document types, and includes applicant data forms. The application was developed using the waterfall method, which involved requirement analysis, design, development, testing, and implementation stages. The Microsoft Access-based official document storage application has an attractive interface, is user-friendly, has fast response times, includes a security system, and most importantly, can store document data centrally within a single application. Further development may involve adding additional features.